2016
DOI: 10.3390/ani6050034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Androstenone on Leash Pulling and Jumping Up in Dogs

Abstract: Simple SummaryBehavior problems such as leash pulling and jumping up are common reasons given for relinquishing dogs to animal shelters. Interomones are chemical signals produced by one species that elicit an effect on a different species; this study examines the effects of androstenone (produced by boars) on dog leash pulling and jumping up behavior. Androstenone in spray form reduces leash pulling behavior compared to a control spray. This interomone may provide instant relief for behavioral problems and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Various training approaches have been suggested for treating jumping up. For instance, stopping the dog from jumping by stepping on a lead [59], spraying the jumping dog with androstenone-infused water [60], or, more importantly, teaching alternative responses (e.g., sitting or lying on a mat) when a person enters the premises [58,61,62]. However, these training approaches have been put forward in absence of establishing the cause of jumping or, in an ABA context, without conducting a FBA prior to the onset of the intervention.…”
Section: The Current Studymentioning
confidence: 99%
“…Various training approaches have been suggested for treating jumping up. For instance, stopping the dog from jumping by stepping on a lead [59], spraying the jumping dog with androstenone-infused water [60], or, more importantly, teaching alternative responses (e.g., sitting or lying on a mat) when a person enters the premises [58,61,62]. However, these training approaches have been put forward in absence of establishing the cause of jumping or, in an ABA context, without conducting a FBA prior to the onset of the intervention.…”
Section: The Current Studymentioning
confidence: 99%
“…Androstenone (more on this molecule below) will stop dogs from barking ( 26 ) or leash pulling ( 30 ). We do not know of an anti-barking pheromone in dogs, yet the phenomenon is real—the molecule changes dog behavior.…”
Section: Organs That Sense Semiochemicalsmentioning
confidence: 99%
“…The same authors earlier showed that androstenone can change the brain chemistry of horses by changing blood serotonin, cortisol, and β-endorphin concentrations ( 50 ). Androstenone also stops dogs from barking or jumping or leash pulling ( 26 , 30 ). We do not know if androstenone is a pheromone in dogs, horses, or humans, but investigators have reported changes in behavior and physiology after androstenone exposure in each of these species ( 26 , 27 , 48 ).…”
Section: Semiochemicals In Domestic Pigsmentioning
confidence: 99%
“…Dogs often lunge forwards during on-leash walks, which may damage the soft tissue around the neck and trachea [ 38 ] and contribute to increased intraocular pressure [ 39 ]. In addition, leash reactivity is reported to be a common problem after adoption [ 37 ] and is related to the failure of dog ownerships [ 40 ].…”
Section: Introductionmentioning
confidence: 99%